Optimization of the gas leak monitoring points distributed underground. (May 2017) - Hou, Longfei; Qian, Xinming; Du, Bingxuan; Yuan, Mengqi
Abstract: It is crucial to monitor gas concentration in an explosive underground space with the utmost accuracy and in real time; unfortunately, this involves a large number of costly monitoring points. This article proposes a novel method for optimizing gas leak monitoring points in a flexible manner per real-time monitoring requirements. The method accounts for leakage diffusion radius, effective monitoring length, and other relevant influence factors. The probability distribution function is utilized to describe the leakage diffusion radius, which can be used to calculate the effective monitored length by taking the expectation of any section of the pipeline as the actual monitored length. The method was tested and the results were analyzed, then improved upon via the optimal effective monitored length distribution. The proposed method was applied to a 356-m-long concrete road with 121 inspection wells to find that the minimum amount of monitoring points is 60 and the maximum effective monitored length is 274.7 m. If the effective monitored length was reduced by 0.12%, the amount of monitoring points could be decreased to 50. The theoretical optimization scheme is 229.1 m in effective monitored length and 19 monitoring points. The proposed method represents a novel approach to preventing pipeline leakage. It allows for real-time, low-cost monitoring of gas concentration in the surrounding underground space near the pipeline, as well as for optimizing the distribution of monitoring points. Highlights: An optimization method was proposed to select the monitor points detect the gas concentration of the pipeline. The probability function describes the diffusion distance after the buried gas pipeline leaking was carried out. The computation method to calculate the effective monitoring length of the pipeline was conducted. The case study shows that the optimization method can effectively reduce the amount of monitor points. The method raises the chances of safely monitoring the maximum length of the gas pipeline with a relatively low cost.